2011
DOI: 10.4049/jimmunol.1101757
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Transcription Factor c-Rel Is Required for Th17 Effector Cell Development in Experimental Autoimmune Encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a T cell-mediated autoimmune disease involving effector Th subsets such as Th1 and Th17. In this study, we demonstrate that mice lacking the NF-κB transcription factor family member c-Rel (rel−/−), which are known to be resistant to EAE, show impaired Th17 development. Mixed bone marrow chimeras and EAE adoptive transfer experiments show that the deficiency of effector Th17 cells in rel−/− mice is T cell intrinsic. Consistent with this finding, c-Rel was activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 50 publications
2
59
1
Order By: Relevance
“…To our surprise, the expression of these factors was not influenced by Malt1 deficiency. Recent studies have suggested that c-Rel, which may act downstream of MALT1, controls Th17 cell differentiation by inducing RORγ and RORγt expression (53,54). However, in our experimental system, MALT1 appeared to act independently of c-Rel, as we did not detect any changes in c-Rel protein levels or in RORγt expression in Malt1 -/-Th cells.…”
Section: Discussioncontrasting
confidence: 47%
“…To our surprise, the expression of these factors was not influenced by Malt1 deficiency. Recent studies have suggested that c-Rel, which may act downstream of MALT1, controls Th17 cell differentiation by inducing RORγ and RORγt expression (53,54). However, in our experimental system, MALT1 appeared to act independently of c-Rel, as we did not detect any changes in c-Rel protein levels or in RORγt expression in Malt1 -/-Th cells.…”
Section: Discussioncontrasting
confidence: 47%
“…This suggests that MALT1 protease activity modulates signaling events downstream of the CBM complex without completely abrogating canonical NF-kB signaling (via the IKK-IkB axis). It is interesting to observe that the alterations in the T and B cell compartments identified in Malt1 PD/PD mice closely resemble those reported in c-Rel-deficient animals (23,(39)(40)(41)(42). Moreover, c-Rel was also shown to regulate IL-21 production and T FH cell differentiation (43).…”
Section: Discussionmentioning
confidence: 52%
“…39 Loss of c-REL has also been shown to prevent pathology in mouse models of collageninduced arthritis, 46 streptozotocin-induced diabetes 47 and autoimmune encephalomyelitis. 48 These outcomes can be explained by the involvement of Th1 cytokines and/or IL-17 in these diseases, because their production and the differentiation of Th1, 49 as well as Th17 48 effector T cells, are c-RELdependent. The fact that c-REL is also critical for cytokine production by macrophages, dendritic cells and NKT cells 12 is also likely to contribute to the reduced pathology in FasL 27 However, no data on animal lifespan were provided and these mice were on a mixed genetic background; notably, genetic background greatly affects pathology in Fas lpr/lpr mice.…”
Section: Discussionmentioning
confidence: 99%